Land scarcity, rural livelihoods and forest management in West Usambara, Tanzania - Songoro, Alexander Elias; Justus Liebig University Giessen (My University, 2014)
This PhD research was conducted in West Usambara (northeastern Tanzania) in Lushoto District, Tanga Region. The area is characterized by high population density; mountainous nature, and tropical rain forests which are rich in biodiversity. These features have largely influenced the availability of arable land, especially for agricultural activities. The research aimed at analyzing the inter-linkages between land, rural livelihoods, and forest management. It thus sought to provide answers to the following specific questions: (i) How does land scarcity impact on rural livelihoods and wealth accumulation in West Usambara? (ii)What are the community responses towards land scarcity in West Usambara? (iii) What is the perception of local communities towards forest management and its outcomes in relation to forest conditions? And; (iv) What are the current forests conditions in West Usambara and what kind of pressures are they experiencing?The researcher used a Sustainable Livelihoods Framework (SLF) to guide the investigation. Both socio-economic and vegetation survey methods were employed to capture data for comprehending different themes in relation to land, rural livelihood and forest management. The research came up with the following findings among others: the community of West Usambara is far from achieving sustainable livelihood. This is because the area has limited sustainable livelihoods opportunities due to scarcities in livelihood resources such as arable land. Hence, it experiences poor performance of livelihood strategies which contribute to low wealth accumulation, low socio-economic status, food insecurity, low income, high out-migration and land conflicts especially on field borders. The area has slim opportunities to improve people´s wellbeing. Thus different adaptation mechanisms embarked on earlier, have done little to improve the situation.With respect to forests, the current forest management contributes to the decline in the consumption patterns of forest products and the number of people who engage in forest based livelihoods activities (FBLA). To pursue FBLA, people engage in illegal activities inside forest reserves which cause wasteful forest utilization. Consequently, forest conditions are deteriorating as manifested in the form of large extent of illegal activities inside the reserve forests, illegal mining inside forest reserves, decline of forest canopy cover, alteration in the structure and composition of some tree species, and low basal areas. These happen despite the fact that more people have positive attitudes towards forest conservation especially entailing environmental benefits associated with forests conservation.Therefore, the research provides several recommendations for policy consideration: villages‟ governments should mobilize villagers in need of arable land and forward their application of land to the government. Together with earmarking them arable land, the support in forms of agricultural credits and promotion of off-farm activities is also imperative. These initiatives apart from increasing household‟s land size and solving unemployment problem it would also promote food security. Moreover, the government should also promote land administration through provision of legal education to the members of the village land councils and ward tribunals which will help to minimize land conflicts.With respect to forests management, the government should sign Joint Forest Management Agreements with the villagers and give clarification on how villagers participating in forest conservation would benefit. Also, the government should start to provide the financial incentives to the forest guards and village committees. In addition, scaling-up the ongoing reducing emission from deforestation and forest degradation (REDD) initiatives in Tanzania to West Usambara is required. Such initiatives would motivate villagers to engage in conservation as it ensures some economic incentives.

Diese Dissertation wurde in West Usambara (im Nordosten Tansanias), im Lushoto District in der Region Tanga durchgeführt. Das Gebiet ist durch eine hohe Bevölkerungsdichte, Gebirgslandschaft und tropischen Urwald mit hoher Biodiversität gekennzeichnet. Diese Charakteristika haben einen starken Einfluss auf die Verfügbarkeit landwirtschaftlich nutzbarer Flächen und deren Nutzung für agrarwirtschaftliche Aktivitäten. Das Ziel dieser Arbeit war es, die Zusammenhänge zwischen den einzelnen Faktoren zu analysieren. Die Arbeit zielte ferner darauf ab, Lösungsansätze zu folgenden Fragen bereitzustellen: (i) Welchen Einfluss hat die Landknappheit auf das Leben der Landbevölkerung und deren Wohlstand? (ii) Wie reagiert die Bevölkerung West Usambaras auf die Landknappheit? (iii) Wie lässt sich die Wahrnehmung und die Position der lokalen Bevölkerung hinsichtlich der Waldwirtschaft beschreiben? (iv) In welchem Zustand befindet sich gegenwärtig der Wald im Westen Usambaras und welchen Umwelteinflüssen ist er ausgesetzt?Die vorliegende Arbeit verwendet das Modell Sustainable Livelihoods Framework (SLF) . Um die Charakteristika des Landes, der ökonomischen und physischen Existenzgrundlage der Bevölkerung und der Waldwirtschaft zu verstehen, wurden sozioökonomische und vegetationsorientierte Untersuchungsmethoden verwendet. Die Ergebnisse der Untersuchung waren unter anderem: Die Gesellschaft von West Usambara ist weit davon entfernt, nachhaltige Lebensbedingungen zu etablieren. Der Grund dafür ist, dass das Gebiet wegen der Knappheit an agrarisch nutzbarem Land die Möglichkeiten zu nachhaltigem Leben einschränkt. Die schwach ausgeprägten ökonomischen Grundlagen haben einen Einfluss auf den niedrigen Wohlstand, den niedrigen sozioökonomischen Status, die Lebensmittelknappheit, das niedrige Einkommen, die hohe Emigration und beinhalten ein erhebliches Konfliktpotential um benachbarte Felder. Die Region bietet wenige Möglichkeiten, um die Lebensqualität zu verbessern. Verschiedene Adaptionsmechanismen haben bisher kaum die Situation positiv beeinflusst, auch wenn diese bereits seit längerem angewendet wurden.In Bezug auf den Wald hat die zuständige Forstverwaltung zu einer Verringerung der forstlich erzeugten Produkte ebenso beigetragen, wie zu einer Reduzierung der im Wald ökonomisch aktiven Bevölkerung. Um Forest Based Livelihoods Activities (FBLA) zu umgehen, sind viele Menschen in illegale Aktivitäten im Wald verstrickt, die die Ressourcen des Waldes verstärkt verschwenden. Folglich verschlechtert sich der Zustand des Waldes weiterhin. Illegale Aktivitäten in Reservaten, unerlaubter Minenbetrieb innerhalb des Schutzgebietes, der Rückgang der Vegetationsdecke, Eingriffe in den Lebensraum spezieller Baumarten und Basalgebiete haben einen erheblichen Anteil daran. Dies alles geschieht trotz einer überwiegend positiven Einstellung gegenüber dem Schutz des Waldes und der Befürwortung des Erhaltes.Daher bietet die Arbeit mehrere politische Verbesserungsvorschläge: Kommunalverwaltungen sollten ihre Einwohner dazu animieren, ihre Ansprüche an kulturfähiges Land gegenüber der Regierung geltend zu machen. Die Bindung der Menschen an Kulturland sollte durch Agrarkredite und off farm activities weiter gefördert werden. Neben der Vergrößerung der zur Verfügung stehenden Grundstücksflächen pro Haushalt sowie der Verringerung der Arbeitslosigkeit würde eine solche Konzeption ferner die Nahrungsmittelsicherheit verbessern. Darüber hinaus sollte die Regierung die regionale Verwaltung durch die Verbesserung des Bildungssystems unterstützen. Wenn hierdurch die Mitglieder der Gemeinderäte und der Gerichte unterstützt würden, könnte dies Konflikte über die Landnutzung verringern.Im Kontext der Forstverwaltung sollte die Regierung Forstgesetze bzw. Forstnutzungsrechte erlassen, wodurch in der Bevölkerung Klarheit über die Teilnahme an Schutzbestrebungen geschaffen werden würde und die Bevölkerung eigene Vorteile darin erkennt. Des Weiteren sollte der Staat Finanzierungsanreize gegenüber den Einwohnern und der Forstverwaltung verbessern. Außerdem wäre eine Korrektur der reducing emission from deforestation and forest degradation (REDD) im Westen Usambaras hilfreich. Derartige Initiativen würden die Bevölkerung auch ökonomisch zum Erhalt der Natur motivieren.
Landknappheit, ländliche Lebensbedingungen und Waldmanagement in West Usambara, Tansania
Keywords: Landknappheit; ländliche Lebensbedingungen; Waldmanagement; West Usambara; Tansania; land scarcity; rural livelihoods; forest management; West Usambara; Tanzania; ddc:550